The Scope and Application of the Concept of Public Social Spending in the Colombian Legal System - Rojas Cabeza, Angélica Johanna (DIXI, 2014)
Ths article is the result of a research project completed by the author in 2012. It focuses on the degree of uncertainty of the concept of public social spending, through the analysis of the evolution of legislation, jurisprudence and doctrine, including an exhaustive review of comparative law and observing the implementation of public social spending in the Department of Santander. Th methodology described by professor Diego López in the book “Th Right of Judges” is used to make the jurisprudential analysis, presenting the following question: Is there a defiition of public social spending in the jurisprudence of the Constitutional Court that can clarify the uncertainty of the concept expressed in the Letter? Is there a defiition of public social spending in the jurisprudence of the Constitutional Court that can broaden the concept expressed in the Letter and clarify the uncertainty generated through the art. 41 of the eop? It is concluded that in the national context, the concept is uncertain, unknowing the intension of the fist constituent and, in the local context, the existence of a considerable margin of discretionality from the administration regarding its application was observed.
Keywords: Social State under the Rule of Law; Public Social Spending; public fiances; social investment.